2012
DOI: 10.1645/ge-2943.1
|View full text |Cite
|
Sign up to set email alerts
|

New Species of Arostrilepis (Eucestoda: Hymenolepididae) In Members of Cricetidae and Geomyidae (Rodentia) from the Western Nearctic

Abstract: : Specimens originally identified as Arostrilepis horrida from the Nearctic are revised, contributing to the recognition of a complex of cryptic species distributed across the Holarctic region. Previously unrecognized species are described based on specimens in cricetid (Neotominae) and geomyid rodents. Arostrilepis mariettavogeae n. sp. in Peromyscus californicus from Monterey County, California and Arostrilepis schilleri n. sp. in Thomomys bulbivorus from Corvallis, Oregon are characterized. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 18 publications
(34 reference statements)
0
21
0
Order By: Relevance
“…Faunal assembly involving temporal and geographic mosaics related to recurrent events of geographic expansion and contact among potential host groups and host switching appear to be important drivers in establishing regional assemblages of cestodes among rodents (e.g., Haukisalmi et al 2010b;Hoberg et al 2012;Makarikov et al 2012). For example, among hymenolepidids, the genus Arostrilepis appears to be the sister of tapeworms among Soricomorpha with origins then attributable to host colonization of Arvicolinae (e.g., Haukisalmi et al 2010a); subsequent diversification reflects episodes of host colonization among geomyid and neotomine rodents (e.g., Makarikov et al 2012;Hoberg et al 2012).…”
Section: Hymenolepidid Diversity Among Rodentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Faunal assembly involving temporal and geographic mosaics related to recurrent events of geographic expansion and contact among potential host groups and host switching appear to be important drivers in establishing regional assemblages of cestodes among rodents (e.g., Haukisalmi et al 2010b;Hoberg et al 2012;Makarikov et al 2012). For example, among hymenolepidids, the genus Arostrilepis appears to be the sister of tapeworms among Soricomorpha with origins then attributable to host colonization of Arvicolinae (e.g., Haukisalmi et al 2010a); subsequent diversification reflects episodes of host colonization among geomyid and neotomine rodents (e.g., Makarikov et al 2012;Hoberg et al 2012).…”
Section: Hymenolepidid Diversity Among Rodentsmentioning
confidence: 99%
“…For example, among hymenolepidids, the genus Arostrilepis appears to be the sister of tapeworms among Soricomorpha with origins then attributable to host colonization of Arvicolinae (e.g., Haukisalmi et al 2010a); subsequent diversification reflects episodes of host colonization among geomyid and neotomine rodents (e.g., Makarikov et al 2012;Hoberg et al 2012). Considering H. folkertsi, morphological similarity among Nearctic species is observed for H. tualatinensis in a geomyid from central Oregon, H. pitymi in an arvicoline from Tennessee, and H. robertrauschi in species of Onychomys a related neotomine, and putative sister of Peromyscus, across west-central North America from southern Canada to northern Mexico.…”
Section: Hymenolepidid Diversity Among Rodentsmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional 10 molecular-based lineages of Aros-trilepis have been correlated with unequivocal morphological attributes. Among these, nominal Arostrilepis now include 5 endemic species in the Palearctic (and a minimum of 1 undescribed), 4 endemic species in the Nearctic, 2 species with amphiberingian distributions spanning northwestern North America and northeastern Eurasia, and one species with a disjunct distribution that includes localities in Europe and northwestern North America (Cook et al 2005;Makarikov et al , 2012Makarikov et al 2013). Our studies have clearly demonstrated the value of integrated morphological/molecular approaches in exploring the distribution and limits of species diversity relative to host associations and geography.…”
Section: Introductionmentioning
confidence: 77%
“…Among these, A. horrida in the Palearctic, and A. mariettavogeae Makarikov, Gardner et Hoberg, 2012 andA. schilleri Makarikov, Gardner et Hoberg, 2012 in the Nearctic are based solely on morphological criteria (Makarikov et al , 2012). An additional 10 molecular-based lineages of Aros-trilepis have been correlated with unequivocal morphological attributes.…”
Section: Introductionmentioning
confidence: 99%